PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI DINAS KETENAGAKERJAAN KOTA MEDAN - Lubis, Rini; Pardede, Finsen; Sibarani, Mario; Napitupulu, R.B (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2023)
Stress and motivation are factors that also influence the decrease or increase in employee performance. The purpose of this study was to determine and analyze the effect of stress and motivation on the performance of dinas ketenagakerjaan kota medan. The author limits the problem only to the effect of stress and work motivation on employee performance at the dinas ketenagakerjaan kota medan. Formulation of the problem whether work stress and work motivation affect employee performance at the dinas ketenagakerjaan kota medan, the population in this study totaled 58 people as the sample. The type of this research is quantitative research, with secondary data and distributing questionnaires to respondents as a data source. The data analysis method used is multiple linear regression analysis, hypothesis testing is done by Partial Test (t), Simultaneous Test (F) and Determination Coefficient Test (R2). The results of this study are Y = 0.550 + 0.447 X1 + 0.398 X2. The stress variable has a partial effect on employee performance. This can be seen from the significant value of 0.001 <0.05 and the t-count value of 3.543 > t-table 1.673. The motivation variable has a partial effect on employee performance, this can be seen from the significant value of 0.002 <0.05 and the t-count value of 3.225 > t-table 1.673, the hypothesis is accepted. The variables of stress and work motivation simultaneously have a positive and significant effect on employee performance. This can be seen from the resulting sig value of 0.000 <0.05 and the Fcount value of 34.156 while Ftable is 3.17 so Fcount > Ftable. Based on the test results of the coefficient of determination (R2) it is known that the R square value is 0.554 which means that the influence of stress and motivation variables on performance variables is 55.4%. It means having a relationship that is not too strong. While the remaining 44.6% is caused by other factors outside the research.